The epistolary of D. I. Yavornitsky as a reflection of development of the Ukrainian language in Katerinoslav region (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
Vocabulary of epistolary texts of the end of the 19th – the beginning of the 20th century is analyzed in the article on the material of the epistolary heritage of D.I.Yavornitsky and his correspondents, namely common lexis, lexical and semantic characteristics of dialect lexis, vulgarisms, the use of borrowed words and book vocabulary, particularly Old Church Slavonic words.
Keywords: epistolary; common lexis; colloquial lexis; dialectisms; vulgarisms; Latinisms; Russian borrowed words; Old Church Slavonic words